2019
DOI: 10.3233/jad-190853
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Transfer Ameliorates Cognitive Deficits, Neuronal Loss, and Gliosis in Alzheimer’s Disease Mice

Abstract: Pathogenesis of neurodegenerative diseases involves dysfunction of mitochondria, one of the most important cell organelles in the brain, with its most prominent roles in producing energy and regulating cellular metabolism. Here we investigated the effect of transferring active intact mitochondria as a potential therapy for Alzheimer's disease (AD), in order to correct as many mitochondrial functions as possible, rather than a mono-drug related therapy. For this purpose, AD-mice (amyloid-␤ intracerebroventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 67 publications
3
63
0
Order By: Relevance
“…SZRD increases the hippocampal neurons in CA3 and DG of APP/PS1 transgenic mice AD's pathological feature is the loss of in hippocampal neurons [34]. Hippocampal neurons are the biological basis of hippocampal-dependent learning and memory.…”
Section: The Action Of Szrd In Ameliorating Cognitive Dysfunction In App/ps1 Transgenic Micementioning
confidence: 99%
“…SZRD increases the hippocampal neurons in CA3 and DG of APP/PS1 transgenic mice AD's pathological feature is the loss of in hippocampal neurons [34]. Hippocampal neurons are the biological basis of hippocampal-dependent learning and memory.…”
Section: The Action Of Szrd In Ameliorating Cognitive Dysfunction In App/ps1 Transgenic Micementioning
confidence: 99%
“…Restoration of mitophagy and inhibition of mitochondrial fission-promoting factor Drp1, whose interaction with Aβ results in defective mitophagy, might be beneficial for preventive neuronal death and cognitive deficits in Alzheimer’s type neurodegeneration [ 43 ]. However, some studies [ 44 ] have revealed that mitophagy is inhibited in neurons in Alzheimer’s disease, and stimulation of mitophagy might have a positive effect on the cognitive functions of experimental animals. Therefore, the exact role of aberrant mitophagy in neuronal damage in Alzheimer’s disease needs further clarification.…”
Section: Mitochondrial Dysfunction and Nvu/bbb Impairment In Alzheimer’s Type Neurodegenerationmentioning
confidence: 99%
“…In addition to therapies attacking amyloid-beta, targeting mitochondrial dysfunction may indirectly ameliorate AD pathology. Nitzan and colleagues have attempted mitochondrial transplantation to restore mitochondrial function in a mouse AD model produced by Aβ 1-42 intracerebroventricular infusion (Nitzan et al, 2019). Mitochondria isolated from HeLa cells were injected through the tail vein.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Moreover, mitochondrial functional parameters in the liver and brain were also restored. Collectively, mitochondrial transplantation through IV route can be a new therapeutic strategy for AD (Nitzan et al, 2019).…”
Section: Alzheimer's Diseasementioning
confidence: 99%